Mobile Automation Testing Framework and QA Dashboard - Atienza, Troy (Wellington Faculty of Engineering Symposium, 2023)
This project has two parts. The first is on the evaluation and implementation of an automation testing framework for a mobile application, Onsite, and the second is on the design and creation of a dashboard for the QA team. Onsite is a mobile application for property valuations in India with a focus on alleviating its complex, inaccurate, or missing property addressing. However, the lack of automation in Onsite could lead to erroneous code leaking to releases. Moreover, the cost and time in finding and fixing bugs post-release is significantly higher than prevention through automated tests. Therefore, the first part of the project was on the evaluation and implementation of an automation testing framework for Onsite. The results of the evaluation have proven to be sufficient as it can produce the functionalities of the application in the testing scripts efficiently. The testing framework utilizes WebdriverIO, Appium, and BrowserStack. However, divergence occurred from the original goal after Onsite faced major changes that would invalidate the efforts of automation, resulting in the shift in focus from the implementation phase to code architecture, readability, and structure, instead of code coverage. As for the second part of the project, the QA Dashboard, the results are satisfactory as per stakeholder feedback. Moreover, it is evident that the QA Dashboard is satisfactory as it fulfils the original goal of providing an overview for the QA team and its managers. Specifically, the managers can utilize the dashboard during stakeholder sessions to show the status of automation within the squads and projects, while the QA team is able to determine priorities for the upcoming sprints based on areas lacking manual or automated testing.